Performa Tanaman Kelapa Sawit pada Musim Kering di Sumatera Selatan; Pengaruh Defisit Air terhadap Fenologi Tanaman - Sherly Agustiana; Ruli Wandri; Dw Asmono (Seminar Nasional Lahan Suboptimal, 2018)
Agustiana et al, 2019. Performance of Oil Palm in Dry Sesason in South Sumatera: Effect of Water Deficit on Plant Phenology. pp. 67-73.South Sumatra has a Monsoon type of rainfall that is a clear difference between the rainy and the dry season. Rainfall distribution cause successive dry months resulting in a water deficit. Water deficit can affect the performance of oil palm. The purpose of this study was to determine the phenology response of the appearance of midribs, male and female flowers to the variability of the season in South Sumatra. This study used a completely randomized design with 2 genotypes is Nigeria 3 and Nigeria 4 with 2 replications so that there were 4 units of experimental plots, where each plot consisted of 12 palms. Based on the results of observations it is known that plants that experience stress due to water deficit are indicated by the number of spear leaves> 4, and decrease of female flowers.